Go, little green truck! - Schotter, Roni 1946- (Farrar, Straus and Giroux, 2016)
Little Green is a proud and strong pickup truck who loves helping with chores, but when Farmer Gray buys a big new blue truck, Little Green is left to rust in a pasture until the farmer's daughter, Fern, suggests they fix him up and use him for such gentle jobs as going to the farmers' market